Assessment and risk management cemeteries in Lima Metropolitana and Callao - Araníbar Tapia, Sonia (2012)
Cemeteries are places where people have the bodies for burial. These places must have sanitary technical conditions for the human body does not pose risks to cemetery workers, population and environment, due to their emissions of decomposition of the bodies. The objective of the research is to identify and manage the risks of workers cemeteries, the surrounding population to these areas and the environment, under the guidelines of environmental management, with the aim of contributing to improving the current situation of cemeteries. The research was conducted in a nonrandom sample and deliberate, six cemeteries located in the city of Lima. It has also included three stages: information gathering, risk assessment, and systematization and analysis of information. As part of the methodology was conducted interviews and observations. , Having established criteria for health, welfare, health and environmental low, medium and high: the risks according to three levels were evaluated. We interviewed 30% of workers and 39% of the population living around six cemeteries. Foul include results.